Lumber Drying Model in Traditional Shipbuilding - Patrick, Bayo-Philip; Koto, Jaswar; Siow, C.L (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Indonesian traditional ship is a product of an indigenous technology developed long before the advent of western culture along the Coast of Sulawesi Island. The ships are built traditionally in both method and equipment without any sketches or calculations. Advancement in science and technology, and abundant information available on the World Wide Web has caused unprecedented changes in many areas of human Endeavour. However, Indonesian traditional ship builders have not taken full advantage of available technology and information particularly in the preparation of lumber which remains one of the critical and most unpredictable stages in construction. This study addressed the issue of delays which is always one of the critical issues confronting the construction of traditional ship in Kepulauan Riau. A low cost air drying model was proposed. The model was tested by comparing the air drying time of lumber in two specific conditions. Four different sample s of lumber were used to test the efficiency of both the air drying model and the natural air drying technique. In conclusion, the proposed model having applied and compared with the traditional method clearly show a better method.